24 A SPECIFIC GENE-MICROBE INTERACTION DRIVES THE DEVELOPMENT OF EARLY-ONSET CROHN'S DISEASE-LIKE COLITIS. (7th February 2019) - Caruso, Roberta; Mathes, Tailor; Martens, Eric C; Kamada, Nobuhiko; Nusrat, Asma; Inohara, Naohiro; Núñez, Gabriel
Abstract: Crohn's disease (CD) is a chronic relapsing intestinal inflammatory disorder that results from an abnormal mucosal immune response against intestinal bacteria in genetically susceptible individuals. Several susceptibility genes have been linked to CD, most of which are involved in host responses to bacteria. Although associated with CD, it is unclear whether dysbiosis is a consequence of intestinal inflammation or plays a causal role in disease. It is also uncertain whether overall dysbiosis or specific bacteria trigger disease in genetically susceptible individuals. To address these questions, we used mutant mice that harbor mutations in two anti-microbial genes associated with increased susceptibility to CD (i.e. Nod2 and phagocyte NAPDH oxidase) to study host-microbial interactions required for disease development. No signs of intestinal inflammation occurred in single-mutant mice; however, a combined deficiency in Nod2 and phagocyte NAPDH oxidase activity triggers early-onset spontaneous TH 1-type intestinal inflammation in mice with the pathological hallmarks of CD. The pathogenesis of disease is driven by a gram-negative anaerobic bacterium that is typically found in the colonic mucus layer of normal mice. The absence of these two anti-microbial genes leads to a marked accumulation of this bacterium in the gut associated with impaired recruitment of neutrophils and killing of the organism by luminal neutrophils. Mutant mice are protected from disease by maternal immunoglobulins against this bacterium during nursing. Our results provide the first evidence that a specific intestinal microbe can trigger CD-like disease in the presence of impaired clearance of the bacterium by innate immunity.